2011
DOI: 10.1007/s00266-011-9789-6
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Scar Mastopexy with a Cat’s Tail Extension for Prevention of Skin Redundancy: An Experience with 17 Consecutive Cases After Mastopexy and Mastopexy with Breast Augmentation

Abstract: The cat's tail marking is a simple modification of the vertical scar mastopexy that eliminated redundant skin in the current series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Introduction of cat’s tail modification to vertical scars, selection of incision based on preoperative nipple-areolar complex to inframammary crease measurements, limited use of periareolar markings for mastopexy, and finally‚ the use of layered mastopexy with augmentation have all contributed to reduced complication and revision rates and to achieve full potential of mastopexy with augmentation in MSBP. 27 , 28 , 34 , 35 The development of layered mastopexy with augmentation is a journey that started with the use of the MSBP, and further improvement is expected to continue in the future to reduce complication and revision rates. 16 , 27 Layered mastopexy with augmentation showed that the procedure was performed as a day case in 90.2% of patients who underwent layered mastopexy with augmentation compared with 54.3% of patients who underwent nonlayered mastopexy with augmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of cat’s tail modification to vertical scars, selection of incision based on preoperative nipple-areolar complex to inframammary crease measurements, limited use of periareolar markings for mastopexy, and finally‚ the use of layered mastopexy with augmentation have all contributed to reduced complication and revision rates and to achieve full potential of mastopexy with augmentation in MSBP. 27 , 28 , 34 , 35 The development of layered mastopexy with augmentation is a journey that started with the use of the MSBP, and further improvement is expected to continue in the future to reduce complication and revision rates. 16 , 27 Layered mastopexy with augmentation showed that the procedure was performed as a day case in 90.2% of patients who underwent layered mastopexy with augmentation compared with 54.3% of patients who underwent nonlayered mastopexy with augmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of the procedure [1,2] , single stage mastopexy with augmentation's overall safety, outcome and complications are compared when the augmentation mammoplasty or mastopexy is performed alone [3][4][5][6][7][8] . Intrinsically singlestage mastopexy with augmentation is a combination of two procedures [9] , the augmentation, in which an implant is placed in any pocket [9][10][11][12][13][14] and the mastopexy, where markings can be selected on the basis of surgeon's experience [5][6][7]16] . The challenging aspect of the surgery is the combination of the two procedures where mastopexy is performed to reduce and tighten the breast skin envelope and breast implant is placed to expand skin envelope and enhance breast cup size, both being diagonally opposite [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Scar selection for mastopexy can be a surgeon's choice. However, it is not without its impact on the outcome leading to revision surgeries [5,15,16] . There is a lack of information where a technique has been defined for the preservation of the function of breast, the safety of the procedure along with the restoration of normal breast morphometry leading to a predictable aesthetic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…[5] This method involves splitting the pectoralis major in the line of its fibres to gain access to the submuscular plane as opposed to division of the pectoralis major along the infra-mammary fold [ Figure 4]. The technique has been described for primary [6][7][8][9] and secondary procedures. [10][11][12] The technique not only reduces the dynamic deformity due to absence of muscle release but also has been described to correct dynamic deformity associated with partial sub muscular or dual plane augmentation mammoplasty.…”
Section: Discussionmentioning
confidence: 99%